2019
DOI: 10.3390/app9091888
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Accuracy of Fault Frequency by Means of Local Mean Decomposition and Ratio Correction Method for Rolling Bearing Failure

Abstract: The fault frequencies are as they are and cannot be improved. One can only improve its estimation quality. This paper proposes a fault diagnosis method by combining local mean decomposition (LMD) and the ratio correction method to process the short-time signals. Firstly, the vibration signal of rolling bearing is decomposed into a series of product functions (PFs) by LMD. The PF, which contains the richest fault information, is selected to perform envelope spectrum analysis by the Hilbert transform (HT). Secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The ratio correction method uses the ratio of two spectral lines with a difference of 1 near the peak of the main lobe of the window spectral function after frequency normalization to establish an equation with the normalized correction frequency as a variable, solve the normalized correction frequency, and then perform spectrum correction 19 , 20 . If the spectral function of the normalized window function is W1(f1), then the amplitude of the window spectral function is W1(f1).…”
Section: Double Correction Methods Of Spectrum Signalmentioning
confidence: 99%
“…The ratio correction method uses the ratio of two spectral lines with a difference of 1 near the peak of the main lobe of the window spectral function after frequency normalization to establish an equation with the normalized correction frequency as a variable, solve the normalized correction frequency, and then perform spectrum correction 19 , 20 . If the spectral function of the normalized window function is W1(f1), then the amplitude of the window spectral function is W1(f1).…”
Section: Double Correction Methods Of Spectrum Signalmentioning
confidence: 99%
“…This model can be implemented in real time for monitoring failures in roller bearings. 93 A frequency matching linear transform technique is reported for bearing fault detection under variable rotating speeds 94 and Huffman coding technique is also used to identify bearing defect severity. 95…”
Section: Decision Tree Random Forest Ensemble Modelmentioning
confidence: 99%
“…Bearing elements fault detection: This Special Issue includes eight excellent examples of improving bearing fault detection. In the first paper, Duan et al [39] improved the fault detection rate of a general rolling bearing by combining the local mean decomposition (LMD) and the ratio correction methods. Then, Cui et al [40] discussed the diagnosis of multiple defects in a rolling bearing via vibration analysis; Shi et al [41] reported a frequency matching linear transform technique for bearing fault detection under variable rotating speeds; moreover, Yin et al [42] proposed a Huffman coding technique to identify bearing defect severity.…”
Section: Contentmentioning
confidence: 99%